2015
DOI: 10.4067/s0717-95022015000300037
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Foramen Location and Lingula Height in Dentate Dry Mandibles, and its Relationship With Cephalic Index

Abstract: SUMMARY:The mandibular foramen and its lingula is a major landmark when administering anesthetic or performing surgical procedures. The objective of this study was to determine whether the topological features of the mandibular foramen (MF) and lingula varied in mandibles from skulls of different cephalic indexes. The location of the mandibular foramen referred to the longitudinal borders of the mandibular ramus (MR), height of the foramen (Hf) referred to the occlusal line of the second molar, and the height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
0
5
0
11
Order By: Relevance
“…It is important to note that the level at which the lingula is found varies among individuals. 23 Panoramic radiographs could provide guidance for locating the position of the lingula and the mandibular foramen. 14 22 24 Kim et al 10 reported that the tip of the lingula coincided with the level of the deepest point of the coronoid notch in 82.0% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the level at which the lingula is found varies among individuals. 23 Panoramic radiographs could provide guidance for locating the position of the lingula and the mandibular foramen. 14 22 24 Kim et al 10 reported that the tip of the lingula coincided with the level of the deepest point of the coronoid notch in 82.0% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A língula por sua vez é uma estrutura que apresenta variações na sua forma e tamanho, ocasionando riscos de lesão a importantes estruturas nervosas durante a realização da técnica 7,8 . A literatura mostra diversos trabalhos relacionados ao estudo das dimensões do ramo da mandíbula 5,[12][13][14][15][16] . Com relação a altura do ramo, os valores encontrados por Fernandes et al (12) foram 49,49mm (dolicocéfalo), 48,25mm (mesocéfalo) e 48,01mm (braquicéfalo).…”
Section: Tipo Craniométricounclassified
“…A literatura mostra diversos trabalhos relacionados ao estudo das dimensões do ramo da mandíbula 5,[12][13][14][15][16] . Com relação a altura do ramo, os valores encontrados por Fernandes et al (12) foram 49,49mm (dolicocéfalo), 48,25mm (mesocéfalo) e 48,01mm (braquicéfalo). Ennes e Medeiros13 encontrou 46,6mm do lado direito e 48,8mm do lado esquerdo.…”
Section: Tipo Craniométricounclassified
See 2 more Smart Citations